Using the consolidated framework for implementation research to understand safety net health system efforts to increase colorectal cancer screening rates. Issue 4 (2nd July 2018) - Kegler, Michelle C; Beasley, Derrick D; Liang, Shuting; Cotter, Megan; Phillips, Emily; Hermstad, April; Williams, Rentonia; Martinez, Jeremy; Riehman, Kara
Abstract: Guided by the Consolidated Framework for Implementation Research (CFIR), this study aimed to identify factors that influence implementation of evidence-based provider and client-oriented strategies to promote colorectal cancer (CRC) screening in safety net health systems. Site visits and key informant interviews ( n =33) were conducted with project leaders and staff in five health systems funded by an American Cancer Society grants program. Within- and cross-site analyses identified CFIR constructs that influenced implementation of provider and client-oriented strategies to promote CRC screening through colonoscopies and fecal immunochemical tests. Of the five CFIR domains, constructs within four CFIR domains (inner setting, outer setting, individual characteristics and process domains) were particularly salient in discussions of implementation while constructs within one CFIR domain (characteristics of the intervention) were not. This study provides a detailed description of how facilitating and inhibiting factors influenced the implementation of evidence-based practices related to CRC screening within safety net health systems. These findings can inform future efforts to promote evidence-based strategies to increase CRC screening rates in safety net health systems.